Muscle activity and acute stress in fibromyalgia - Zetterman, Teemu (BMC Musculoskelet Disord, 2021)
BACKGROUND: Fibromyalgia (FM) patients are likely to differ from healthy controls in muscle activity and in reactivity to experimental stress. METHODS: We compared psychophysiological reactivity to cognitive stress between 51 female FM patients aged 18 to 65 years and 31 age- and sex-matched healthy controls. They underwent a 20-minute protocol consisting of three phases of relaxation and two phases of cognitive stress. We recorded surface electromyography normalized to maximum voluntary muscle contraction (%EMG), the percentage of time with no muscle activity (EMG rest time), and subjective pain and stress intensities. We compared group reactivity using linear modelling and adjusted for psychological and life-style factors. RESULTS: The FM patients had a significantly higher mean %EMG (2.2 % vs. 1.0 %, p < 0.001), pain intensity (3.6 vs. 0.2, p < 0.001), and perceived stress (3.5 vs. 1.4, p < 0.001) and lower mean EMG rest time (26.7 % vs. 47.2 %, p < 0.001). In the FM patients, compared with controls, the pain intensity increased more during the second stress phase (0.71, p = 0.028), and the %EMG decreased more during the final relaxation phase (-0.29, p = 0.036). Within the FM patients, higher BMI predicted higher %EMG but lower stress. Leisure time physical activity predicted lower %EMG and stress and higher EMG rest time. Higher perceived stress predicted lower EMG rest time, and higher trait anxiety predicted higher pain and stress overall. CONCLUSIONS: Our results suggest that repeated cognitive stress increases pain intensity in FM patients. FM patients also had higher resting muscle activity, but their muscle activity did not increase with pain. Management of stress and anxiety might help control FM flare-ups. TRIAL REGISTRATION: Retrospectively registered on ClinicalTrials.gov (NCT03300635).